Approach and Application of the Roblox Application as a Learning Medium - Ida Faridah; Changjiang Deng (Yayasan Adra Karima Hubbi, 2024)
The use of Roblox as a learning medium has gained significant attention due to its interactive, game-based platform. This study investigates the effectiveness of Roblox as a digital learning tool and explores how it can positively impact students’ learning experiences. The research employs a quantitative method, formulating statements into a Google Form survey to gather data from students, which is then analyzed using SPSS. The study aims to determine whether Roblox enhances student engagement and helps solve learning challenges. Results indicate that Roblox can significantly increase student involvement in discussions and raise interest in learning activities through its interactive features. Additionally, it aids in addressing both internal and external factors affecting students. The conclusion of the study suggests that Roblox offers an effective and engaging alternative for improving learning quality in higher education. Educators are encouraged to explore and understand the application’s potential to maximize its benefits in the classroom. Overall, the study highlights that Roblox has the potential to enhance student learning experiences and could be a valuable tool in modern education.